Mobile Multimedia Processing Fundamentals, Methods, and Applications - Jiang, Xiaoyi; Ma, Matthew Y.; Chen, Chang Wen.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Whereas the mobile device has become ubiquitous in people's daily life not only as a cellular phone but also as a media player, a mobile computing device, and a personal assistant, it is particularly important to address challenges timely in applying advanced pattern recognition, signal, information and multimedia processing techniques, and new emerging networking technologies to such mobile systems. The 15 articles in this state-of-the-art survey foster interdisciplinary discussions and research in mobile multimedia processing techniques, applications and systems, and bring stimulus to researchers on pushing the frontier of emerging new technologies and applications. This book constitutes the thoroughly refereed post-workshop proceedings of the First International Workshop on Mobile Multimedia Processing, WMMP 2008, held in Tampa, FL, USA, in December 2008, in conjunction with ICPR 2008, the 19th International Conference on Pattern Recognition. The papers went through two rounds of reviewing and improvement and are organized in topical sections on accessibility and learning, server assisted adaptation and networking applications, entertainment, face and speech processing, and development environment.
Accessibility and Learning -- iFeeling: Vibrotactile Rendering of Human Emotions on Mobile Phones -- Mobile Visual Aid Tools for Users with Visual Impairments -- QR Code and Augmented Reality-Supported Mobile English Learning System -- Server Assisted Adaptation and Networking Applications -- Robust 1-D Barcode Recognition on Camera Phones and Mobile Product Information Display -- Evaluating the Adaptation of Multimedia Services Using a Constraints-Based Approach -- Mobile Video Surveillance Systems: An Architectural Overview -- Hybrid Layered Video Encoding for Mobile Internet-Based Computer Vision and Multimedia Applications -- Entertainment -- A Recommender Handoff Framework for a Mobile Device -- MuZeeker: Adapting a Music Search Engine for Mobile Phones -- A Server-Assisted Approach for Mobile-Phone Games -- Face and Speech Processing -- A Face Cartoon Producer for Digital Content Service -- Face Detection in Resource Constrained Wireless Systems -- Speech Recognition on Mobile Devices -- Development Environment -- Developing Mobile Multimedia Applications on Symbian OS Devices -- Developing Mobile Applications on the Android Platform.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Information systems; Multimedia systems; Telecommunication; Computer Science; Computer Communication Networks; Multimedia Information Systems; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Communications Engineering, Networks